Clear cell adenocarcinoma of the male urethra: clinical case report - Juliana Sinezio Santos; Gabriella Oliveira Mendes; Fernando Sabino Marques Monteiro (Brazilian Journal of Oncology)
Primary clear cell adenocarcinoma of the urethra is a rare malignancy and most of the cases described are in women. The symptomatology is similar to other tumors of the urethra. Because it is a rare malignancy and the consequent lack of trials in the medical literature, there is no data about the most appropriate treatment for this disease. We aim to describe a clinical case of primary clear cell adenocarcinoma of the urethra in a young male patient. This is a 36-year-old male diagnosed with primary clear cell adenocarcinoma of the urethra whom underwent a surgery for localized disease and about 30 months later he had a local and systemic recurrence. He was treated with platinum-based chemotherapy and presented an excellent clinical and radiological response. Although there is no optimal treatment for this malignancy, in the case of metastatic disease, systemic platinum-based chemotherapy should be considered an appropriate option.